2018
DOI: 10.1038/s41396-018-0296-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term succession in a coal seam microbiome during in situ biostimulation of coalbed-methane generation

Abstract: Despite the significance of biogenic methane generation in coal beds, there has never been a systematic long-term evaluation of the ecological response to biostimulation for enhanced methanogenesis in situ . Biostimulation tests in a gas-free coal seam were analysed over 1.5 years encompassing methane production, cell abundance, planktonic and surface associated community composition and chemical parameters of the coal formation water. Evidence is presented that sulfate reducing bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 97 publications
0
41
0
Order By: Relevance
“…Hydrocarbon-degrading Bacteria (HCB) are hence potential candidates to utilize or cometabolize these types of plastics ( Dussud et al, 2018b ; Basili et al, 2020 ; Erni-Cassola et al, 2020 ). HCB use linear, branched, or aromatic hydrocarbons as sole energy, and carbon source and are often found in oil reservoirs, oil seeps, or oil spills ( Joye et al, 2014 ), contaminated sediments ( Kimes et al, 2013 ) and coal beds ( Beckmann et al, 2019 ), but they are also found ubiquitously in the marine environment ( Yakimov et al, 2007 ; Erni-Cassola et al, 2020 ; Thompson et al, 2020 ). Although HCB are often detected on plastic ( Wright et al, 2020 ), previous investigations seldomly focus on the potential role of HCB as MPD degraders ( Erni-Cassola et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocarbon-degrading Bacteria (HCB) are hence potential candidates to utilize or cometabolize these types of plastics ( Dussud et al, 2018b ; Basili et al, 2020 ; Erni-Cassola et al, 2020 ). HCB use linear, branched, or aromatic hydrocarbons as sole energy, and carbon source and are often found in oil reservoirs, oil seeps, or oil spills ( Joye et al, 2014 ), contaminated sediments ( Kimes et al, 2013 ) and coal beds ( Beckmann et al, 2019 ), but they are also found ubiquitously in the marine environment ( Yakimov et al, 2007 ; Erni-Cassola et al, 2020 ; Thompson et al, 2020 ). Although HCB are often detected on plastic ( Wright et al, 2020 ), previous investigations seldomly focus on the potential role of HCB as MPD degraders ( Erni-Cassola et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The red square indicates the corresponding taxa found in this study had 98% or higher identity to the sequences in CSMB reference set and co-occurred across a range of published studies. a [80], b [45], c [22], d [14], e [81], f [15], g [82], h [11], i [83], j [13], k [84], l [63]…”
Section: Discussionmentioning
confidence: 99%
“…One of the highly abundant OTUs (Operational Taxonomic Unit) observed in this 16S rRNA amplicon sequence based study was taxonomically identified as a pseudomonad (OTU_9), and its presence during early colonisation suggested it may play some role in degrading organic matter in coal. Interestingly, Pseudomonas species have been previously identified from almost all surveys of coal seams conducted to date 6,1225 and pseudomonads isolated from coals in the past have been reported for the production of biosurfactants 26 and lignin degradation phenotypes 27 . Additionally, a previous study has noted the prevalence of seemingly aerobic taxa and metabolisms in deep anoxic hydrocarbon environments 28 .…”
Section: Introductionmentioning
confidence: 99%